2020
DOI: 10.1038/s41598-020-74774-7
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Subungual Glomus Tumors with 18 MHz Ultrasound and CDFI

Abstract: To evaluate the imaging features of subungual glomus tumors using 18 MHz high-frequency ultrasound with CDFI (Color Doppler Flow Imaging). 20 patients treated by surgical resection and examined by ultrasound between January 2008 and December 2019. All eligible cases are divided into two groups: Group A used the probe frequency of 9–14 MHz from January 2008 to December 2014, and Group B used the probe frequency of 18 MHz from January 2015 to December 2019. Patient demographics, clinical records, pathologic spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
0
6
0
4
Order By: Relevance
“…Moreover, it has been reported that glomus tumors with presurgical ultrasound present lower rates of recurrence in comparison with the one non previously studied. [10][11][12][13][111][112][113][114][115][116][117]…”
Section: Glomus Tumormentioning
confidence: 99%
“…Moreover, it has been reported that glomus tumors with presurgical ultrasound present lower rates of recurrence in comparison with the one non previously studied. [10][11][12][13][111][112][113][114][115][116][117]…”
Section: Glomus Tumormentioning
confidence: 99%
“…CDFI technology can increase the speci city of ultrasound by providing real-time vascular assessment. [24,25] In our study, CDFI was signi cantly different between benign and malignant lymph nodes, and the richer the lymph node blood supply, the higher probability of malignant LNs.…”
Section: Discussionmentioning
confidence: 47%
“…CDFI technology can increase the specificity of ultrasound by providing real-time vascular assessment [ 25 , 26 ]. In our study, CDFI was significantly different between benign and malignant lymph nodes, and the richer the lymph node blood supply, the higher probability of malignant LNs.…”
Section: Discussionmentioning
confidence: 99%